Boosting physical education performance: how attitude and motivation instruments impact student success - Nugraha, Ugi; Budiarti, Retni Sulistiyoning; Yuliawan, Ely (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2025)
Background: The motivation of students plays a crucial role in their academic success by fostering enthusiasm and willingness to learn. Understanding the relationship between attitude, motivation, and learning outcomes is essential for enhancing educational practices. However, there is a need to investigate this relationship specifically in the context of high school students in Jambi City, where physical education (PE) is a vital component of the curriculum. Research Objectives: This study aims to explore the relationship between attitude, motivation, and learning outcomes among high school students in Jambi City. By employing a quantitative approach, the research seeks to analyze the extent to which attitude and motivation impact students’ PE learning outcomes. Methods: A sample of 120 high school students from Jambi City was selected through saturated sampling. Data collection methods included observation, interviews, questionnaires, and documentation. The research utilised various analytical techniques, including correlation analysis, prerequisite tests (normality and linearity tests), descriptive statistical analysis, and hypothesis testing (simple correlation, multiple correlation, significance tests—F-tests, and coefficients of determination). Findings/Results: The findings reveal a positive and significant relationship between attitude, motivation, and the PE learning outcomes of high school students in Jambi City. Descriptive analysis indicates generally positive attitudes and high motivation levels among the students. Correlation analysis demonstrates that both attitude and motivation contribute significantly to PE learning outcomes, with higher levels of attitude and motivation correlating with better outcomes. Conclusion: The study underscores the importance of attitude and motivation in influencing PE learning outcomes among high school students in Jambi City. These findings highlight the need for educational interventions that focus not only on academic content but also on fostering positive attitudes and motivation to enhance student engagement and performance in PE.